Preface [to] Information systems and technology for organizational agility, intelligence, and resilience - Rahman, Md. Hakikur (2014)
Information Systems and Technology for Organizational Agility, Intelligence, and Resilience aims to advise and support organizational agents who want ensure success in terms of financial, social, and environmental aspects, as well as in the aspect of human development, in a more sustainable way. The premier reference work provides examples of conceptual research, methodologies, empirical cases, and success cases for academics, researchers, intermediaries, and organizations looking to use information systems and technology to boost their agility, intelligence, and resilience.